Hemodialysis vs peritoneal dialysis : comparison of net survival in incident patients on chronic dialysis in Colombia (2021)
Background: In the area of nephrology, the practical application of relative survival methodologies can provide information regarding the impact of outcomes for patients with kidney failure on dialysis compared with what would be expected in the absence of this condition. Objective: Compare the net survival of hemodialysis (HD) and peritoneal dialysis (PD) patients in a cohort of incident patients on chronic dialysis in Colombia, according to the dialysis therapy modality. Design: Observational, analytic, historical cohort. Setting: Renal Therapy Services (RTS) clinic network across Colombia. Patients: Patients over 18 years old with chronic kidney disease, incidents in dialytic therapy, which reached day 90 of therapy. Recruitment took place from January 1, 2008, to December 31, 2013, with a follow-up until December 31, 2018. The final cohort for analysis corresponds to a total of 12508 patients, of which 5330 patients (42.6%) began HD and 7178 patients (57.4%) began PD. Measurements: Demographic, socioeconomic, and clinical variables were measured. Methods: Analyses were conducted according to the treatment assigned (PD or HD) at the time of the inception of the cohort and another approach of analysis was done with a subsample of those patients who never changed the initial modality. To calculate expected survival, life tables were constructed for Colombia for the years 2006 to 2018. Net survival estimates were made using the Pohar Perme estimator. The comparison of the net survival curves was done using the method developed by Pavlič and Perme, the log-rank type. Results: Net survival at 5 years compared with the general population was estimated at 0.53 (95% confidence interval 0.52-0.54) in the dialysis cohort. In intention-to-treat analyses of 7178 patients on PD and 5330 patients on HD, by global and Pohar-Perme methods, survival (expressed as a ratio of survival in patients on dialysis to survival in an age-, sex- and geographic-matched general Colombian population) was higher in patients on HD than in those on PD. In year 1, net survival by Pavlov-Perme on PD was 0.79 (95% confidence intervals [CI] 0.78 - 0.80) and on HD 0.85 (95% CI 0.84 - 0.86); in year 5, 0.36 (95% CI 0.34 – 0.38) and 0.57 (95% CI 0.55 – 0.59) for PD and HD respectively. Limitation: There may be imbalances among the populations analyzed (HD vs PD), in which one or more variables other than the type of therapy may influence the survival of the patients. In Colombia there are marginal levels of underreporting of demographic data in some subpopulations that may affect life-tables construction. Conclusion: An important difference was observed in terms of survival between the dialysis population and the population of reference without dialysis. Statistically significant differences were found in net survival between HD and PD, net survival was higher in patients on HD than in those on PD.